Eicosapentaenoic and Docosahexaenoic Acids Differentially Alter Gut Microbiome and Reverse High‐Fat Diet–Induced Insulin Resistance. Issue 10 (4th May 2020) - Zhuang, Pan; Zhang, Yu; Shou, Qiyang; Li, Haoyu; Zhu, Ya'er; He, Lilin; Chen, Jingnan; Jiao, Jingjing
Abstract : Scope: To assess the individual effects of dietary eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on insulin resistance (IR), gut microbiome, and gut metabolites in high‐fat‐diet‐induced obese (DIO) mice. Methods and results: DIO mice are fed an either high‐fat diet (HFD), EPA (1% w/w) enriched HFD, or DHA (1% wt/wt) enriched HFD for 15 weeks. Both EPA and DHA supplements reverse hyperglycemia and IR but do not affect body weight in DIO mice while DHA exhibits a more pronounced ameliorative effect in male mice. Both EPA‐ and DHA‐enriched Lactobacillus and short‐chain fatty acids (SCFAs)‐producing species from Lachnospiraceae while reduced lipopolysaccharide (LPS)‐producing Bilophil a and Escherichia/Shigella . Compared with EPA, DHA‐supplemented mice have more abundant propionic/butyric acid‐producing bacteria, including Coprococcus, Butyricimonas synergistica, Bacteroides acidifaciens, and Intestinimonas, and less‐abundant LPS‐correlated species Streptococcus and p‐75‐a5 . The shifts in gut microbiome co‐occurred with the changes in levels of propionic/butyric acid, circulating LPS, and serotonin. Additionally, EPA/DHA supplementation attenuates adipose inflammation with upregulated glucose transporter 4 and Akt phosphorylation, indicating the improvement of insulin signaling. Conclusion: EPA and DHA differentially reverse IR and relieve adipose inflammation while modulating gut microbiome and SCFAs/LPS production, underscoring the gut‐adipose axis as a primary target of EPA/DHA. Abstract : Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) differentially modulate the gut microbiome and reverse obesity‐related insulin resistance. The more beneficial effect for DHA is related to the more profound enrichment in propionic/butyric acid‐producing bacteria and reduction in lipopolysaccharide‐correlated (LPS) species, which co‐occur with changes in gut metabolites and leads to improved adipose inflammation and insulin signaling.